Perancangan Interior Restaurant China – Dayak Di Kalimantan Barat - Marselinda Puspita; Stephanus P Honggowidjaja (Intra, 2018)
The restaurant is a general term used to describe a business that serves a dish to communities and provide a place to enjoy these dishes as well as set specific rates for food and services. In the present era, it can be seen that the culinary development has been very rapidly, such as in the area of the city – the city has many areas that are strategic for the restaurant. This design will design a modern restaurant serving Chinese food that will be focused on the usual Pontianak regional food is famous for its Chinese – Dayak.Pontianak is the city's famous haven't quite brought more food or a restaurant that only serves but also selling atmosphere. A restaurant with an interior that will appeal to make consumers interested to come and perform the activity, with the menu and atmosphere are qualified to make the consumer want to come to enjoy it, with the emergence of restaurants in a variety of concept.                This restaurant design gives service system with unique atmosphere which differs from other restaurants. There is a dessert area where every customer can enjoy the served dessert. The showcase in that area is decorated with Kain Tenun and traditional vases to attract customers. The purpose of this design is to educate people to know Pontianak unique craft and history.